Predictors of external branch of superior laryngeal nerve paresis and paralysis in patients undergoing thyroidectomy: by videostroboscopy - Manoj Kumar N.; Rajiv S.R.; T. M. Nagaraj; Sweta S.; Ramya K.; Pavitra N. (The Egyptian Journal of Otolaryngology)
Abstract Background Thyroidectomy is one of the most commonly done surgery in otorhinolaryngology; hence, a pre-operative analysis of the recurrent laryngeal nerve and superior laryngeal nerve functions of laryngeal musculature is very important. A retrospective analysis was done to detect pre-operative external branch of superior laryngeal nerve (EBSLN) paresis and paralysis in patients undergoing thyroidectomy secondary to benign and malignant pathology and to outline the importance of stroboscope before all thyroid surgeries on 51 patients with thyroid pathologies, planned for thyroidectomy in a tertiary care center in a span of 2 years who underwent video-laryngeal stroboscope pre-operatively to detect pre-operative external branch of superior laryngeal nerve paresis and paralysis and relationship with thyroid diagnosis. Results Thirty-six cases (70%) had normal findings, whereas 9 patients (18%) had EBSLN paresis and 6 cases (12%) had EBSLN paralysis. Signs suggestive of unilateral paresis and unilateral paralysis are asymmetry of folds, irregularity of vocal folds, incomplete glottic closure and mid phonatory gap, reduced mucosal wave pattern of affected vocal fold, reduced amplitude, paralyzed cords vertical plane was off level compared to normal, anterior bowing of vocal folds, tilting of anterior glottis to the affected side, concavity of vocal folds, and short and flaccid vocal folds. Conclusion Pre-operative stroboscope should be done in all cases who undergo thyroid surgery since it helps in identifying early paresis and palsy. Superior laryngeal nerve paresis and paralysis are relatively common but traditionally difficult to diagnose with certainty. Video laryngeal stroboscope is a useful tool in the evaluation of patients with suspected laryngeal paralysis and justifies an intrinsic relationship that exists between thyroid diseases and EBSLN paresis and paralysis which is related to local effects of the disease resulting in reduced stiffness in the paralyzed cord. The reliable predictors of worsening paresis are malignant lesions and suspected benign to malignant pathologies.